Differentiate or Die: 3-Bromopyruvate and Pluripotency in Mouse Embryonic Stem Cells - Rodrigues, Ana Sofia (2015)
Pluripotent embryonic stem cells grown under standard conditions (ESC) have a markedly glycolytic profile, which is shared with many different types of cancer cells. Thus, some therapeutic strategies suggest that pharmacologically shifting cancer cells towards an oxidative phenotype, using glycolysis inhibitors, may reduce cancer aggressiveness. Given the metabolic parallels between cancer and stemness would chemotherapeutical agents have an effect on pluripotency, and could a strategy involving these agents be envisioned to modulate stem cell fate in an accessible manner? In this manuscript we attempted to determine the effects of 3-bromopyruvate (3BrP) in pluripotency. Although it has other intracellular targets, this compound is a potent inhibitor of glycolysis enzymes thought to be important to maintain a glycolytic profile. The goal was also to determine if we could contribute towards a pharmacologically accessible metabolic strategy to influence cell differentiation. Methodology/Principal Findings Mouse embryonic stem cells (mESC) grown under standard pluripotency conditions (in the presence of Leukemia Inducing Factor- LIF) were treated with 3BrP. As a positive control for differentiation other mESCs were grown without LIF. Overall our results demonstrate that 3BrP negatively affects pluripotency, forcing cells to become less glycolytic and with more active mitochondria. These changes in metabolism are correlated with increased differentiation, even under pluripotency conditions (i.e. in the presence of LIF). However, 3BrP also significantly impaired cell function, and may have other roles besides affecting the metabolic profile of mESCs. Conclusions/Findings Treatment of mESCs with 3BrP triggered a metabolic switch and loss of pluripotency, even in the presence of LIF. Interestingly, the positive control for differentiation allowed for a distinction between 3BrP effects and changes associated with spontaneous differentiation/ loss of pluripotency in the absence of LIF. Additionally, there was a slight differentiation bias towards mesoderm in the presence of 3BrP. However, the side effects on cellular function suggest that the use of this drug is probably not adequate to efficiently push cells towards specific differentiation fates.